Potential CO2 forcing and Asian summer monsoon precipitation trends during the last 2,000 years - Ren Weihe; Li Quan; Qin Feng; Yi Guitian (Open Geosciences, 2021)
Holocene records for the Asian Summer Monsoon (ASM) indicate that, apart for the last 2,000 years (“2 kyr shift”), solar insolation was the dominant factor controlling the monsoon climate. The aim of this review is to provide a synopsis of climate characteristics over the last 2 kyr, clarifying mechanisms for the diverse trend with Northern Hemisphere Summer Insolation (NHSI) records. Here, we initially review proxy-based climate reconstructions for the last 2 kyr, and then compare them with records from the last five interglacial periods. Finally, we examine potential physical mechanisms responsible for the “2 kyr shift.” Findings from this review indicate that the “2 kyr shift” is a representative pattern of Holocene climate change within the core area of the ASM, and the “2 kyr shift” could be mainly controlled by changes in atmospheric CO2 concentration. In addition, suggestions to address a more humid condition dominating the Asian monsoonal margin zones are offered.